1993
DOI: 10.1103/physrevlett.71.2634
|View full text |Cite
|
Sign up to set email alerts
|

Possible solution of the conductivity exponent puzzle for the metal-insulator transition in heavily doped uncompensated semiconductors

Abstract: The electrical conductivity o (extrapolated to T=0) of uncompensated Si:P indicates a crossover as a function of P concentration TV at TV cr slightly above the metal-insulator transition at TV C . For TV > TV cr the exponent of a-(N-N c )' i is // ~ 0.64, while n « 1.3 for N c < TV < TV cr . At TV cr do/dT changes sign from negative for TV > TV cr to positive for TV < TV cr . o in a magnetic field also yields pi ~ 1. The apparent discrepancy between uncompensated and compensated semiconductors is traced back t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
163
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(183 citation statements)
references
References 33 publications
17
163
3
Order By: Relevance
“…Refs. [13][14][15][16][17][18]. However, several studies have pointed to inconsistencies of the zero-temperature extrapolations inherent in the critical-exponent determination [8,12,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [13][14][15][16][17][18]. However, several studies have pointed to inconsistencies of the zero-temperature extrapolations inherent in the critical-exponent determination [8,12,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…5 at the T 0 metal-insulator transition in Si:P has remained a puzzle for over a decade [1]. Stupp et al [2] recently have proposed a reanalysis of the Hence, the 6% smaller n, required by Stupp et al to raise p would not permit a self-consistent treatment of the observed critical behavior on both sides of the metal-insulator transition. …”
mentioning
confidence: 99%
“…5 at the T 0 metal-insulator transition in Si:P has remained a puzzle for over a decade [1]. Stupp et al [2] recently have proposed a reanalysis of the data which gives p = 1 [2] is dominated by a nonrandom impurity distribution and should not be compared with the usual theories of critical phenomena.…”
mentioning
confidence: 99%
“…[7], reasons for the earlier experiments not agreeing with one another have been traced to difficulties in having a system allowing sufficient access into the critical region and possessing a well defined critical point. In contrast, the current work is done on a system where the critical point can be clearly identified, and the critical region is experimentally accessible.…”
mentioning
confidence: 99%
“…Therefore, the emphasis has been to obtain the conductivity as a function of T , as close to T = 0 as possible. In spite of intense efforts over several decades [7] it turned out to be rather difficult to access the critical regime in a reliable way. While so far all such experiments confirm the continuous nature of the transition, the values of the critical exponents remain controversial.…”
mentioning
confidence: 99%